Composite aluminum sol as well as preparation method and application thereof

By using the composite aluminum sol method in the preparation of aluminum sol, the slow release of silicon source and cerium source microcapsules is used to control the hydrolysis rate, and the problems of uncontrollable particle size and poor repeatability in the preparation of traditional aluminum sol are solved, and the preparation of composite aluminum sol with high stability and uniform particle size is achieved.

CN119771285AActive Publication Date: 2025-04-08YUEYANG JUCHENG CHEM CO LTD
View PDF 10 Cites 0 Cited by

Patent Information

Application Number
CN202510275306.6
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-03-10
Publication Date
2025-04-08
Estimated Expiration
2045-03-10

AI Technical Summary

Technical Problem

The traditional aluminum sol preparation method has problems such as uncontrollable particle size and poor repeatability, and the molecules of the organic aluminum source are large, resulting in the particle size of the prepared aluminum sol and insufficient stability and mechanical strength.

Method used

The preparation method of composite aluminum sol is adopted, and the aluminum source, silicon source microcapsules and cerium source microcapsules are hydrolyzed under stirring conditions to control the hydrolysis rate to prepare composite aluminum sol with uniform particle size and stable properties.

Benefits of technology

The stability and mechanical strength of the aluminum sol are improved, the uniformity of particle size and the stability of properties are ensured, and the problems of uncontrollable particle size and poor repeatability in traditional methods are solved.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119771285A_ABST
    Figure CN119771285A_ABST
Patent Text Reader

Abstract

The invention belongs to the technical field of preparation of aluminum sol, and particularly relates to composite aluminum sol as well as a preparation method and application thereof. The composite aluminum sol is prepared from the following raw materials in parts by weight: 20 to 30 parts of an aluminum source, 40 to 50 parts of a silicon source microcapsule, 20 to 30 parts of a cerium source microcapsule, 10 to 20 parts of a dispersing agent and 600 to 850 parts of water, the shell material of the cerium source microcapsule is paraffin, and the shell material of the silicon source microcapsule is polymethyl methacrylate. According to the composite aluminum sol provided by the invention, the aluminum source, the silicon source and the cerium source are subjected to composite hydrolysis to form the composite aluminum sol, so that the stability of the aluminum sol is improved; the particle size of the composite aluminum sol is uniform.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of aluminum sol preparation, and specifically relates to a composite aluminum sol and a preparation method and application thereof. Background Art

[0002] Alumina sol is a colloidal solution in which the dispersed phase is extremely fine aluminum hydroxide (Al(OH)3) or aluminum oxide (Al2O3) particles. Alumina sol has many unique properties, such as high specific surface area, good adhesion and film-forming properties, and is therefore widely used in many fields such as catalysis, ceramics, papermaking, and textiles.

[0003] The preparation of aluminum sol usually involves the hydrolysis reaction of aluminum salts (such as aluminum chloride, aluminum sulfate or aluminum nitrate), or the hydrolysis and polycondensation process of aluminum alkoxides (such as aluminum isopropoxide), but the traditional preparation method for preparing aluminum sol has disadvantages such as uncontrollable particle size and poor repeatability. To solve this problem, in the prior art, an organic aluminum source is dissolved in an alcohol solvent, and then hydrolyzed to obtain an aluminum sol. Although this method controls the particle size of the aluminum sol to a certain extent, the speed of aluminum released by the organic aluminum source decreases with the decrease in concentration, and the molecules of the organic aluminum source are relatively large, so that the particle size of the prepared aluminum sol is not uniform. In addition, the yield and product purity of the organic aluminum source will not only affect the preparation of the aluminum sol, but also increase the cost of preparing the organic aluminum source. Summary of the invention

[0004] In order to solve the above problems, the present invention provides a composite aluminum sol and a preparation method and application thereof. The composite aluminum sol has high stability and mechanical strength. The composite aluminum sol prepared by the preparation method has uniform particle size and stable properties.

[0005] The present invention is achieved through the following technical solutions: In a first aspect, the present invention provides a composite aluminum sol, comprising the following raw materials in parts by weight: 20 to 30 parts of aluminum source, 40 to 50 parts of silicon source microcapsules, 20 to 30 parts of cerium source microcapsules, 10 to 20 parts of dispersant and 600 to 850 parts of water; The shell material of the cerium source microcapsule is paraffin, and the shell material of the silicon source microcapsule is polymethyl methacrylate.

[0006] In a second aspect, the present invention provides a method for preparing the composite aluminum sol provided by the present invention, comprising the following steps: Under stirring conditions, the mixed solution is hydrolyzed to obtain a hydrolyzate; the mixed solution includes an aluminum source, a silicon source microcapsule, a cerium source microcapsule, a dispersant and water; The precipitate of the hydrolysis product is obtained, and then washed and aged to obtain a composite aluminum sol.

[0007] In some possible implementations, the stirring condition has a rotation speed of 10 rpm to 30 rpm.

[0008] In some possible implementations, the hydrolysis treatment step includes: The pH value of the mixed solution is adjusted and maintained at 8.5-11.5, and the mixed solution is heated to 60-70° C. at a heating rate of 10° C. / min-30° C. / min and a first heat preservation is performed to obtain a first sol; The pH value of the first sol is adjusted and maintained at 6-8, and the first sol is heated from 60-70° C. to 110-130° C. at a heating rate of 8-10° C. / min. and a second heat preservation is performed to obtain a second sol; The pH value of the second sol is adjusted and maintained at 7-8, and the second sol is heated from 110-130° C. to 150° C. at a heating rate of 5° C. / min-8° C. / min and a third heat preservation is performed to obtain a hydrolyzate.

[0009] In some possible implementations, the preparation of the silicon source microcapsules comprises the following steps: mixing the silicon source suspension and the polymethyl methacrylate solution under stirring conditions at a rotation speed of 30 rpm to 50 rpm, and then performing a first spray drying to obtain silicon source microcapsules; The silicon source suspension contains silicon source and ethanol; and the polymethyl methacrylate solution contains polymethyl methacrylate and acetone.

[0010] In some possible implementations, the temperature of the first spray drying is 60°C to 80°C.

[0011] In some possible implementations, the preparation of the cerium source microcapsules comprises the following steps: mixing the cerium source suspension and molten paraffin under stirring conditions at a rotation speed of 30 rpm to 50 rpm, and then performing a second spray drying to obtain cerium source microcapsules; The cerium source suspension contains a cerium source and ethanol.

[0012] In some possible implementations, the temperature of the second spray drying is 30°C to 40°C.

[0013] In some possible implementations, preparing the mixed solution includes the following steps: mixing and stirring an aluminum source, a silicon source microcapsule, a cerium source microcapsule, a dispersant and water to obtain a mixed solution.

[0014] In a third aspect, the present invention provides an application of the composite aluminum sol provided by the present invention in the fields of catalysis, ceramics, papermaking or textiles.

[0015] Compared with the prior art, the composite aluminum sol and the preparation method thereof provided by the present invention have at least the following beneficial technical effects: (1) The composite aluminum sol provided by the present invention is formed by composite hydrolysis of an aluminum source, a silicon source and a cerium source, thereby improving the stability of the aluminum sol.

[0016] (2) The composite aluminum sol provided by the present invention has uniform particle size and stable properties.

[0017] (3) The preparation method of the composite aluminum sol provided by the present invention is to uniformly disperse the silicon source and the cerium source in water in the form of microcapsules, and then perform segmented hydrolysis under stirring conditions to achieve the purpose of controlling the hydrolysis rate of the mixed solution, thereby preparing a composite aluminum sol with uniform particle size and stable properties. BRIEF DESCRIPTION OF THE DRAWINGS

[0018] In order to more clearly illustrate the embodiments of the present drawings or the technical solutions in the prior art, the drawings required for use in the embodiments or the description of the prior art will be briefly introduced below. Obviously, the drawings described below are only some embodiments of the present drawings. For ordinary technicians in this field, other drawings can be obtained based on the structures shown in these drawings without paying any creative work.

[0019] Figure 1 A TEM image of a composite aluminum sol provided in Example 1 of the present invention; Figure 2 A TEM image of a composite aluminum sol provided in Example 2 of the present invention; Figure 3 This is a TEM image of a composite aluminum sol provided in Example 3 of the present invention; Figure 4 A TEM image of a composite aluminum sol provided in Comparative Example 1 of the present invention; Figure 5 A TEM image of a composite aluminum sol provided in Comparative Example 2 of the present invention; Figure 6 This is a TEM image of a composite aluminum sol provided in Comparative Example 3 of the present invention.

[0020] The purpose, features and advantages of this figure will be further described in conjunction with the embodiments with reference to the accompanying drawings. DETAILED DESCRIPTION

[0021] In order to make the purpose, technical scheme and advantages of the present invention clearer, the present invention is described and illustrated in conjunction with the embodiments below. It should be understood that the specific embodiments described herein are only used to explain the present invention and are not intended to limit the present invention. Based on the embodiments provided by the present invention, all other embodiments obtained by ordinary technicians in this field without making creative work belong to the scope of protection of the present invention.

[0022] Obviously, the following descriptions are only some examples or embodiments of the present invention, and for those of ordinary skill in the art, the present invention can also be applied to other similar scenarios without creative work. In addition, it can also be understood that although the efforts made in such a development process may be complex and lengthy, for those of ordinary skill in the art related to the contents disclosed in the present invention, some changes in design, manufacturing or production based on the technical contents disclosed in the present invention are just conventional technical means, and should not be understood as the contents disclosed in the present invention being insufficient.

[0023] However, unnecessary detailed descriptions may be omitted. For example, detailed descriptions of well-known matters and repeated descriptions of substantially the same structures may be omitted. This is to avoid the following description from becoming unnecessarily lengthy and to facilitate understanding by those skilled in the art. In addition, the following description is provided for those skilled in the art to fully understand the present invention and is not intended to limit the subject matter described in the claims.

[0024] If not otherwise specified, all embodiments and optional embodiments of the present invention may be combined with each other to form a new technical solution, and all technical features and optional technical features of the present invention may be combined with each other to form a new technical solution.

[0025] The following is a detailed description of a composite aluminum sol and a preparation method thereof according to an embodiment of the present invention.

[0026] A first aspect of an embodiment of the present invention provides a composite aluminum sol, comprising the following raw materials in parts by weight: 20 to 30 parts of aluminum source, 40 to 50 parts of silicon source microcapsules, 20 to 30 parts of cerium source microcapsules, 10 to 20 parts of dispersant and 600 to 850 parts of water; The shell material of the cerium source microcapsule is paraffin, and the shell material of the silicon source microcapsule is polymethyl methacrylate.

[0027] The composite aluminum sol provided by the embodiment of the present invention is formed by composite hydrolysis of aluminum source, silicon source and cerium source, so that the composite aluminum sol has high stability. The silicon source microcapsules and cerium source microcapsules use shell materials with different melting points. When preparing the composite aluminum sol, the silicon source and the cerium source can be slowly released, so that the silicon source and the cerium source undergo composite hydrolysis reactions at different temperatures and time periods, which can effectively control not only the hydrolysis conditions but also the hydrolysis rate, and finally prepare a composite aluminum sol with uniform particle size and stable properties.

[0028] In some embodiments, the melting point of paraffin wax is 50°C to 60°C.

[0029] In some embodiments, the melting point of polymethyl methacrylate (PMMA) is 100°C to 120°C.

[0030] In some embodiments, the aluminum source includes at least one of aluminum chloride, aluminum nitrate, and aluminum sulfate.

[0031] In some embodiments, the silicon source includes at least one of sodium silicate and potassium silicate.

[0032] In some embodiments, the cerium source includes at least one of cerium chloride, cerium nitrate, and cerium sulfate.

[0033] In some embodiments, the dispersant includes at least one of sodium dodecyl sulfate (SDS) and sodium dodecylbenzene sulfonate (SDBS).

[0034] A second aspect of an embodiment of the present invention provides a method for preparing a composite aluminum sol provided by an embodiment of the present invention, comprising the following steps: S10. Under stirring conditions, the mixed solution is hydrolyzed to obtain a hydrolysis product; the mixed solution includes an aluminum source, a silicon source microcapsule, a cerium source microcapsule, a dispersant and water.

[0035] S20. Centrifugally separate and obtain the precipitate of the hydrolysis product, and then wash and age it to obtain a composite aluminum sol.

[0036] The method for preparing the composite aluminum sol provided in the embodiment of the present invention is to uniformly disperse the silicon source and the cerium source in water in the form of microcapsules, and then gradually heat the reaction system under stirring conditions, so that the shell materials of the cerium source microcapsules and the silicon source microcapsules are gradually dissolved to release the cerium source and the silicon source therein and hydrolyze, thereby realizing the gradual hydrolysis of the aluminum source, the silicon source and the cerium source, thereby effectively controlling the hydrolysis rate, and further preparing the composite aluminum sol with uniform particle size and stable properties.

[0037] In some embodiments, in the above step S10, the stirring speed is 10 rpm to 30 rpm.

[0038] In some embodiments, in the above step S10, preparing silicon source microcapsules comprises the following steps: S102. Under stirring conditions at a speed of 30 rpm to 50 rpm, the silicon source suspension and the polymethyl methacrylate solution were mixed and first spray-dried to obtain silicon source microcapsules; The silicon source suspension contains silicon source and ethanol; and the polymethyl methacrylate solution contains polymethyl methacrylate and acetone.

[0039] In the above steps of preparing silicon source microcapsules, the silicon source as the core material is made into a silicon source suspension, and the polymethyl methacrylate as the shell material is made into a solution. The suspension and the solution are then mixed and spray-dried. Silicon source microcapsules can be prepared at room temperature, and the prepared silicon source microcapsules have uniform particle size.

[0040] In some embodiments, in the above step S102, preparing the silicon source suspension comprises the following steps: S1021. Stir and mix the silicon source and ethanol to obtain a silicon source suspension.

[0041] In some embodiments, in the above step S102, the mass volume ratio of the silicon source and ethanol is 1g:(1ml~5ml).

[0042] In some embodiments, in the above step S102, preparing the polymethyl methacrylate solution comprises the following steps: S1022. Stir and mix polymethyl methacrylate and acetone to obtain a polymethyl methacrylate solution.

[0043] In some embodiments, in the above step S102, the mass volume ratio of polymethyl methacrylate and acetone is 1g:(10ml~20ml).

[0044] In some embodiments, in the above step S102, the temperature of the first spray drying is 60°C to 80°C.

[0045] In some embodiments, in the above step S10, preparing cerium source microcapsules comprises the following steps: S103. Under stirring conditions at a speed of 30 rpm to 50 rpm, the cerium source suspension and molten paraffin were mixed and then subjected to a second spray drying to obtain cerium source microcapsules; The cerium source suspension contains a cerium source and ethanol.

[0046] In some embodiments, in the above step S103, preparing the cerium source suspension comprises the following steps: S1031. Stir and mix the cerium source and ethanol to obtain a cerium source suspension.

[0047] In some embodiments, in the above step S103, the mass volume ratio of the cerium source and ethanol is 1g:(1ml~5ml).

[0048] In some embodiments, in the above step S103, the temperature of the second spray drying is 30°C-40°C.

[0049] In some embodiments, in the above step S10, preparing the mixed solution comprises the following steps: S104. Mix and stir the aluminum source, silicon source microcapsules, cerium source microcapsules, dispersant and water to obtain a mixed solution.

[0050] In some embodiments, in the above step S10, the hydrolysis treatment step includes: S105. Adjust and maintain the pH value of the mixed solution to 8.5-11.5, heat the mixed solution to 60-70°C at a heating rate of 10-30°C / min, and perform a first heat preservation to obtain a first sol.

[0051] S106. Adjust and maintain the pH value of the first sol to 6-8, heat the first sol from 60-70°C to 110-130°C at a heating rate of 8-10°C / min / min, and perform a second heat preservation to obtain a second sol.

[0052] S107. Adjust and maintain the pH value of the second sol to 7-8, heat the second sol from 110-130°C to 150°C at a heating rate of 5°C / min-8°C / min and perform a third heat preservation to obtain a hydrolyzate.

[0053] In some embodiments, in the above step S105, the first insulation time is 0.5h~1.5h.

[0054] In some embodiments, in the above step S106, the second insulation time is 2h~3h.

[0055] In some embodiments, in the above step S107, the third insulation time is 6h~8h.

[0056] In some embodiments, in the above step S105, a sodium hydroxide solution or a potassium hydroxide solution is used to adjust and maintain the pH value of the mixed solution.

[0057] In some embodiments, in the above step S106, dilute hydrochloric acid or dilute sulfuric acid is used to adjust and maintain the pH value of the first sol.

[0058] In some embodiments, in the above step S107, dilute hydrochloric acid or sodium hydroxide solution is used to adjust and maintain the pH value of the second sol.

[0059] In some embodiments, in the above step S20, the rotation speed of the centrifugal separation is 3000 rpm to 5000 rpm. It should be noted that the rotation speed range shown in the embodiment of the present invention is only an example of the present invention, and the rotation speed of the centrifugal separation can be adjusted according to actual needs and is not limited to the range shown in the embodiment of the present invention.

[0060] In some embodiments, in the above step S20, washing includes the following steps: S201. Under the stirring condition of 20rpm~30rpm, disperse the precipitate in deionized water, heat it to 120℃~130℃, continue stirring for 0.2h~0.5h, and centrifuge to obtain the washed precipitate and washing liquid.

[0061] S202. Repeat step S201 three or more times.

[0062] In the above washing step, after repeating step S201 three times, check whether there are free ions remaining. You can take a small amount of washing liquid and add the corresponding compound for detection. For example, the washing liquid may contain Cl - , then use AgNO3 solution for detection. If there is no precipitation, it means that Cl - Washed clean; the washing liquid may contain SO4 2- , then use Ba 2- Test (if BaCl2 is used, Cl - , then detect SO4 2- ).

[0063] In some embodiments, in the above step S20, aging includes the following steps: S203. Disperse the solid product obtained by washing in deionized water to form a suspension.

[0064] S204. Adjust the pH value of the suspension to 7-7.5.

[0065] S205. Aging for 6h~12h at a stirring speed of 20rpm~30rpm and a temperature of 100℃~120℃.

[0066] The following is further described in conjunction with specific embodiments.

[0067] For the convenience of explanation, in the following examples and comparative examples, unless otherwise specified, the following parameter conditions are adopted: (1) Preparation of silicon source microcapsules: ① Stir and mix the silicon source and ethanol in a mass volume ratio of 1g:2ml to obtain a silicon source suspension.

[0068] ② Stir and mix polymethyl methacrylate and acetone in a mass volume ratio of 1g:15ml to obtain a silicon source suspension.

[0069] ③ Under stirring conditions at a rotation speed of 40 rpm, the silicon source suspension and the polymethyl methacrylate solution are mixed and spray-dried to obtain silicon source microcapsules; the spray drying temperature is 80°C.

[0070] (2) Preparation of cerium source microcapsules: ① Stir and mix the cerium source and ethanol in a mass volume ratio of 1g:3ml to obtain a cerium source suspension.

[0071] ② Under stirring conditions at a rotation speed of 30 rpm, the cerium source suspension and molten paraffin are mixed and spray-dried to obtain cerium source microcapsules; the spray-drying temperature is 40°C.

[0072] (3) The speed of the centrifugal separation involved is 4000 rpm.

[0073] (4) The pH value of the reaction system of the embodiment and comparative example was adjusted using dilute hydrochloric acid or sodium hydroxide solution.

[0074] (5) The washing steps are as follows: ① Under the stirring condition of 30 rpm, disperse the precipitate separated by centrifugation in deionized water, heat it to 120°C, continue stirring for 0.4h, and centrifuge to obtain the washed precipitate and washing liquid.

[0075] ② Repeat the above step ① three times or more until no free anions or cations remain in the washing liquid.

[0076] Example 1 Embodiment 1 provides a composite aluminum sol, which is composed of the following raw materials in parts by weight: 30 parts of aluminum chloride, 50 parts of sodium silicate microcapsules, 20 parts of cerium chloride microcapsules, 20 parts of sodium dodecyl sulfate (SDS) (dispersant) and 700 parts of water.

[0077] Among them, in the silicon-source microcapsules, the shell material is polymethyl methacrylate with a melting point of 120°C; In the cerium source microcapsules, the shell material is paraffin with a melting point of 55°C.

[0078] This embodiment also provides a method for preparing the composite aluminum sol provided in this embodiment, and the steps are as follows: E1. Under stirring conditions at a speed of 20 rpm, the mixed solution was hydrolyzed as follows: E101. Adjust and maintain the pH value of the mixed solution at 9, heat the mixed solution to 65°C at a heating rate of 20°C / min and keep it warm for 1 hour to obtain the first sol.

[0079] E102. Adjust and maintain the pH value of the first sol at 7, heat the first sol from 70°C to 130°C at a heating rate of 10°C / min and keep it warm for 2 hours to obtain a second sol.

[0080] E103. Adjust and maintain the pH value of the second sol at 7, heat the second sol from 130°C to 150°C at a heating rate of 8°C / min and keep it warm for 7 hours to obtain a hydrolysis product.

[0081] E2.Washing and aging: E201. Centrifuge and separate the precipitate of the hydrolyzate, and wash it to obtain a solid product.

[0082] E202. Disperse the solid product in deionized water to form a suspension.

[0083] E203. Adjust the pH value of the suspension to 7~7.5.

[0084] E204. Aged for 12 hours at a stirring speed of 30 rpm and a temperature of 100°C to obtain a composite aluminum sol.

[0085] Example 2 Embodiment 2 provides a composite aluminum sol, which is composed of the following raw materials in parts by weight: 20 parts of aluminum nitrate, 40 parts of sodium silicate microcapsules, 24 parts of cerium nitrate microcapsules, 10 parts of sodium dodecyl sulfate (SDS) (dispersant) and 600 parts of water.

[0086] Among them, in the silicon source microcapsules, the shell material is polymethyl methacrylate with a melting point of 100°C; In the cerium source microcapsules, the shell material is paraffin with a melting point of 50°C.

[0087] This embodiment also provides a method for preparing the composite aluminum sol provided in this embodiment, and the steps are basically the same as those in Example 1, except that: The content of step E1 is as follows: E1. Under stirring conditions at a speed of 10 rpm, the mixed solution was hydrolyzed as follows: E101. Adjust and maintain the pH value of the mixed solution at 10, heat the mixed solution to 60°C at a heating rate of 10°C / min and keep it warm for 1.5 hours to obtain the first sol.

[0088] E102. Adjust and maintain the pH value of the first sol to 8, heat the first sol from 60°C to 110°C at a heating rate of 8°C / min and keep it warm for 3 hours to obtain a second sol.

[0089] E103. Adjust and maintain the pH value of the second sol at 7, heat the second sol from 110°C to 150°C at a heating rate of 5°C / min and keep it warm for 8 hours to obtain a hydrolyzate.

[0090] Example 3 Embodiment 3 provides a composite aluminum sol, which is composed of the following raw materials in parts by weight: 25 parts of aluminum nitrate, 45 parts of potassium silicate microcapsules, 30 parts of cerium nitrate microcapsules, 15 parts of sodium dodecyl sulfate (SDS) (dispersant) and 850 parts of water.

[0091] Among them, in potassium silicate microcapsules, the shell material is polymethyl methacrylate with a melting point of 110°C; In the cerium nitrate microcapsules, the shell material is paraffin with a melting point of 60°C.

[0092] This embodiment also provides a method for preparing the composite aluminum sol provided in this embodiment, and the steps are basically the same as those in Example 1, except that: The content of step E1 is as follows: E1. Under stirring conditions at a speed of 30 rpm, the mixed solution was hydrolyzed as follows: E101. Adjust and maintain the pH value of the mixed solution at 11, heat the mixed solution to 70°C at a heating rate of 30°C / min and keep it warm for 0.5h to obtain the first sol.

[0093] E102. Adjust and maintain the pH value of the first sol at 6, heat the first sol from 70°C to 120°C at a heating rate of 10°C / min and keep it warm for 2.5 hours to obtain a second sol.

[0094] E103. Adjust and maintain the pH value of the second sol at 8, heat the second sol from 120°C to 150°C at a heating rate of 7°C / min and keep it warm for 6 hours to obtain a hydrolyzate.

[0095] Comparative Example 1 Comparative Example 1 provides a composite aluminum sol, which is composed of the following raw materials in parts by weight: 30 parts of aluminum chloride, 50 parts of sodium silicate, 20 parts of cerium chloride and 700 parts of water.

[0096] This comparative example also provides a method for preparing the composite aluminum sol provided in this comparative example, and the steps are as follows: D1-1. Aluminum chloride, sodium silicate, cerium chloride and water are mixed to obtain a mixed solution.

[0097] D1-2. Under stirring conditions at a rotation speed of 20 rpm, the pH value of the mixed solution was adjusted and maintained at 8, and the mixed solution was hydrolyzed at a constant temperature of 100° C. until no precipitation was produced to obtain a hydrolyzate.

[0098] D1-3. The precipitate of the hydrolyzate is obtained by centrifugation and washed to obtain a solid product.

[0099] D1-4. Disperse the solid product in deionized water to form a suspension.

[0100] D1-5. Adjust the pH value of the suspension to 7~7.5.

[0101] D1-6. Aged for 12 h at a stirring speed of 30 rpm and a temperature of 100° C. to obtain a composite aluminum sol.

[0102] Comparative Example 2 Comparative Example 2 provides a method for preparing the composite aluminum sol provided in Comparative Example 1, and the steps are as follows: D2-1. Under the conditions of stirring at a speed of 20 rpm and a constant temperature of 100°C, the pH value of the reaction system was adjusted and maintained at 8. After aluminum chloride was added to the water for hydrolysis, cerium chloride was added for hydrolysis, and finally aluminum silicate was added for hydrolysis until no precipitation was produced to obtain a hydrolysis product.

[0103] D2-2. The precipitate of the hydrolyzate is obtained by centrifugation and washed to obtain a solid product.

[0104] D2-3. Disperse the solid product in deionized water to form a suspension.

[0105] D2-4. Adjust the pH value of the suspension to 7~7.5.

[0106] D2-5. Aged for 12 h at a stirring speed of 30 rpm and a temperature of 100° C. to obtain a composite aluminum sol.

[0107] Comparative Example 3 Comparative Example 3 provides a method for preparing the composite aluminum sol provided in Example 1, and the steps are basically the same as those in Example 1, except that: The content of step E1 is as follows: E1. Under stirring condition with a rotation speed of 20 rpm, the mixed solution was heated to 150°C at a heating rate of 30°C / min and kept warm for 8 h to obtain a hydrolyzate.

[0108] In order to verify the progressiveness of a composite aluminum sol and a preparation method thereof according to an embodiment of the present invention, a transmission electron microscope was used to observe the composite aluminum sol provided in the embodiment and the comparative example. The TEM image is shown in FIG. Figures 1 to 6 After the composite aluminum sol provided in the embodiment and the comparative example was post-treated to obtain a molecular sieve catalyst, the micro-reaction activity of the molecular sieve catalyst was tested experimentally, and the results are shown in Table 1 below.

[0109] The steps of post-treating the composite aluminum sol provided in the embodiment and the comparative example are as follows: drying the composite aluminum sol at 90° C., calcining it at 600° C. in a helium atmosphere for 6 hours, and grinding it to obtain a molecular sieve catalyst with an average particle size of 60 μm.

[0110] The experimental conditions for the micro-reactivity of molecular sieves are: The reaction temperature is 480℃, the catalyst-oil ratio is 3.2, and the weight hourly space velocity is 16 -1 The catalyst loading is 5.0g, the oil input amount is 1.56g, the oil input time is 70s, and the raw oil is Dagang light diesel.

[0111] .

[0112] Attached to the instruction manual Figures 1 to 6 The data in Table 1 above can at least draw the following conclusions:

[0113] (1) Attached to the instruction manual Figures 1 to 6 It can be seen that the particle size of the composite aluminum sol provided by the embodiment of the present invention is uniform and mostly nanoparticles, which means that the silicon source microcapsules and cerium source microcapsules in the embodiment of the present invention use shell materials with different melting points. When preparing the composite aluminum sol, the silicon source and the cerium source can be slowly released, so that the silicon source and the cerium source undergo a composite hydrolysis reaction at different temperatures and time periods, which can effectively control not only the hydrolysis conditions but also the hydrolysis rate, and finally prepare a composite aluminum sol with uniform particle size and stable properties.

[0114] (2) From the comparison of the micro-reaction activities of Examples 1 to 3 and Comparative Examples 1 to 3, it can be seen that the zeolite molecular sieve prepared from the composite aluminum sol of the embodiment of the present invention has a very high micro-reaction activity, improves the raw material conversion rate and the light product yield, and reduces the unit usage of the catalyst.

[0115] It should be noted that the present invention is not limited to the above-mentioned embodiments. The above-mentioned embodiments are only examples, and the embodiments having the same structure as the technical idea and exerting the same effect within the scope of the technical solution of the present invention are all included in the technical scope of the present invention. In addition, without departing from the scope of the main purpose of the present invention, various modifications that can be thought of by those skilled in the art to the embodiments and other methods of combining some of the constituent elements in the embodiments are also included in the scope of the present invention.

Claims

1. A composite aluminum sol, characterized in that: The invention comprises the following raw materials in parts by weight: 20 to 30 parts of aluminum source, 40 to 50 parts of silicon source microcapsules, 20 to 30 parts of cerium source microcapsules, 10 to 20 parts of dispersant and 600 to 850 parts of water; The shell material of the cerium source microcapsule is paraffin, and the shell material of the silicon source microcapsule is polymethyl methacrylate.

2. A method for preparing a composite aluminum sol as claimed in claim 1, characterized in that: The steps include: Under stirring conditions, the mixed solution is hydrolyzed to obtain a hydrolyzate; The mixed solution includes aluminum source, silicon source microcapsules, cerium source microcapsules, dispersant and water; The precipitate of the hydrolysis product is obtained, and then washed and aged to obtain a composite aluminum sol.

3. The method for preparing the composite aluminum sol according to claim 2, characterized in that: The rotation speed of the stirring condition is 10 rpm to 30 rpm.

4. The method for preparing the composite aluminum sol according to claim 2 or 3, characterized in that: The hydrolysis treatment step comprises: The pH value of the mixed solution is adjusted and maintained at 8.5-11.5, and the mixed solution is heated to 60-70° C. at a heating rate of 10° C. / min-30° C. / min and a first heat preservation is performed to obtain a first sol; The pH value of the first sol is adjusted and maintained at 6-8, and the first sol is heated from 60-70° C. to 110-130° C. at a heating rate of 8-10° C. / min. and a second heat preservation is performed to obtain a second sol; The pH value of the second sol is adjusted and maintained at 7-8, and the second sol is heated from 110-130° C. to 150° C. at a heating rate of 5° C. / min-8° C. / min and a third heat preservation is performed to obtain a hydrolyzate.

5. The method for preparing the composite aluminum sol according to claim 4, characterized in that: The preparation of the silicon source microcapsules comprises the following steps: mixing a silicon source suspension and a polymethyl methacrylate solution under stirring conditions of a rotation speed of 30 rpm to 50 rpm, and then performing a first spray drying to obtain silicon source microcapsules; wherein the silicon source suspension comprises a silicon source and ethanol; and the polymethyl methacrylate solution comprises polymethyl methacrylate and acetone.

6. The method for preparing the composite aluminum sol according to claim 5, characterized in that: The temperature of the first spray drying is 60°C to 80°C.

7. The method for preparing the composite aluminum sol according to claim 4, characterized in that: The preparation of the cerium source microcapsules comprises the following steps: mixing a cerium source suspension and molten paraffin under stirring conditions of a rotation speed of 30 rpm to 50 rpm, and then performing a second spray drying to obtain cerium source microcapsules; wherein the cerium source suspension contains a cerium source and ethanol.

8. The method for preparing the composite aluminum sol according to claim 7, characterized in that: The temperature of the second spray drying is 30°C to 40°C.

9. The method for preparing the composite aluminum sol according to claim 8, characterized in that: The preparation of the mixed solution comprises the following steps: mixing and stirring an aluminum source, a silicon source microcapsule, a cerium source microcapsule, a dispersant and water to obtain a mixed solution.

10. Use of the composite aluminum sol as claimed in claim 1 in the fields of catalysis, ceramics, papermaking or textiles.

Citation Information

Patent Citations

  • Aluminosilicate powders

    CA1123815A

  • Method for preparing large surface improved aluminium oxide with high temperature resistant performance

    CN101168125A

  • Preparation of nanometer CeO2-base light catalyst capable of improving degradation performance

    CN101797504A

  • Metal-modified composite molecular sieve, preparation method, and application of metal-modified composite molecular sieve for reaction of preparing propylene and butene through methanol conversion

    CN106179481A

  • Porous alumina matrix with high hydrothermal stability and preparation method thereof

    CN113860344A